Science, technology, society and environment and discursive interactions: problem-posing and joint constructions - Teixeira, Ana Maria; Sutil, Noemi (Revista Hipótese, 2016)
In this work, it is presented considerations about educational proposal to the approach of the relations among science, technology, society and environment, with basis on the assumptions of the communicative action theory, by Jürgen Habermas. Data were constituted by audio records and analyzed considering the study of texts and argumentative discourses. It can be highlighted formative possibilities concerning the involvement of the subjects in problem-posing and proposition of alternatives.
Keywords: Science; technology,; society and environment; Communicative action; Argumentation